Sistema de Reconhecimento de Gestos e Ações em Tempo Real Baseado em Visão Computacional - Santos, Clebeson Canuto dos (2020)
This thesis aims to investigate and propose mechanisms for recognizing and anticipating dynamic gestures and actions based only on computer vision. Three proposals are focused on gesture recognition: Star RGB - a representation that condenses the montion